Evaluation Of Physical Hazard Potential And Health Risk Assessment Using Integrated HRA with ArcGIS® - Favian Hafiz Zain; Bani Isnain Rochmatan Imannudin; Selly Purwasi; Lucky Yudanto Anggoro; Fauzul Azmi; Agrytia Rut Meiriski Aritonang; Eka Fitriani Ahmad (International Journal of Health Engineering and Technology, 2026)
This study evaluates occupational health risks due to exposure to physical factors in the workshop of PT Wesi Kuning Sukses using a quantitative observational design with a cross- sectional approach. The methodology integrates Similar Exposure Groups (SEG), semi- quantitative Health Risk Assessment (HRA), and ArcGIS® spatial modeling. The measurement procedures are based on national technical standard literature studies, including SNI 8427:2017 (noise), SNI 16-7061-2004 (heat), SNI 7062:2019 (lighting), SNI 7054:2019 (vibration), and SNI 16-7060-2004 (UV radiation). The results show noise (93 dBA) and ultraviolet radiation (0.71 µW/cm²) as high-risk priority threats because they exceed the Threshold Limit Value (TLV). Conversely, the parameters of lighting, heat, and vibration are categorized as medium risk according to Permenaker No. 5 of 2018. Spatial analysis identified critical hazard zones within a radius of 0–9 meters, while areas beyond 15 meters were deemed safe for residential use. Although biological monitoring did not reveal acute complaints, latent risks remain. The integration of SEG, HRA, and ArcGIS® proved effective in developing an accurate industrial hygiene management system for long-term occupational health protection.